Compounds from the Fruits of the Popular European Medicinal Plant Vitex agnus-castus in Chemoprevention via NADP(H):Quinone Oxidoreductase Type 1 Induction. (3rd April 2013) - Li, Shenghong; Qiu, Shengxiang; Yao, Ping; Sun, Handong; Fong, Harry H. S.; Zhang, Hongjie
Abstract : As part of our continuing efforts in the search for potential biologically active compounds from medicinal plants, we have isolated 18 compounds including two novel nitrogen containing diterpenes from extracts of the fruits of Vitex agnus-castus . These isolates, along with our previously obtained novel compound vitexlactam A (1 ), were evaluated for potential biological effects, including cancer chemoprevention. Chemically, the nitrogenous isolates were found to be two labdane diterpene alkaloids, each containing an α, β -unsaturated γ -lactam moiety. Structurally, they were elucidated to be 9 α -hydroxy-13(14)-labden-16, 15-amide (2 ) and 6 β -acetoxy-9 α -hydroxy-13(14)-labden-15, 16-amide (3 ), which were named vitexlactams B and C, respectively. The 15 known isolates were identified as vitexilactone (4 ), rotundifuran (5 ), 8-epi-manoyl oxide (6 ), vitetrifolin D (7 ), spathulenol (8 ), cis -dihydro-dehydro-diconiferylalcohol-9-O- β -D-glucoside (9 ), luteolin-7-O-glucoside (10 ), 5-hydroxy-3, 6, 7, 4 ′ -tetramethoxyflavone (11 ), casticin (12 ), artemetin (13 ), aucubin (14 ), agnuside (15 ), β -sitosterol (16 ), p -hydroxybenzoic acid (17 ), and p -hydroxybenzoic acid glucose ester (18 ). All compound structures were determined/identified on the basis of 1D and/or 2D NMR and mass spectrometry techniques. Compounds 6, 8, 9, and 18 were reported from a Vitex spieces for the first time. The cancer chemopreventive potentials of these isolates were evaluated for NADP(H):quinone oxidoreductase type 1 (QR1) induction activity. Compound 7 demonstrated promising QR1 induction effect, while the new compound vitexlactam (3 ) was only slightly active.